2016
DOI: 10.1190/geo2015-0661.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effects of fractures on elastic wave propagation in synthetic layered rocks

Abstract: Fractures greatly increase the difficulty of oil and gas exploration and development in reservoirs consisting of interlayered carbonates and shales and increase the uncertainty of highly efficient development. The presence of fractures or layered media is also widely known to affect the elastic properties of rocks. The combined effects of fractures and layered media are still unknown. We have investigated the effects of fracture structure on wave propagation in interlayered carbonate and shale rocks using phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The approximately N‐S‐aligned normal faults exhibit Gaussian distributions with wide strike orientations ranging from N50°W to N40°E (Figure a). Second, stress‐aligned fluid‐filled fractures in the shale formation (which are often associated with HF stimulation) can produce a fast splitting direction parallel to fracture orientation (Anderson et al, ; Li et al, ; Nolte et al, ). These two types of anisotropy may be distinguishable from their depths: The latter scenario with fractures aligned approximately with the NE‐SW maximum horizontal stress (Figure a) may result in anisotropy in the vicinity of the HF (typically 3‐ to 4‐km depth for Duvernay around Fox Creek), whereas fault‐induced anisotropy could potentially extend from the basement (considering the fault is deep‐seated) to the subsurface and affect the entire ray path.…”
Section: Discussionmentioning
confidence: 99%
“…The approximately N‐S‐aligned normal faults exhibit Gaussian distributions with wide strike orientations ranging from N50°W to N40°E (Figure a). Second, stress‐aligned fluid‐filled fractures in the shale formation (which are often associated with HF stimulation) can produce a fast splitting direction parallel to fracture orientation (Anderson et al, ; Li et al, ; Nolte et al, ). These two types of anisotropy may be distinguishable from their depths: The latter scenario with fractures aligned approximately with the NE‐SW maximum horizontal stress (Figure a) may result in anisotropy in the vicinity of the HF (typically 3‐ to 4‐km depth for Duvernay around Fox Creek), whereas fault‐induced anisotropy could potentially extend from the basement (considering the fault is deep‐seated) to the subsurface and affect the entire ray path.…”
Section: Discussionmentioning
confidence: 99%
“…These were analyzed using a two-layer physical model with a vertical fracture system. The results indicated that the wave velocities usually increase when the fracture aspect ratio is also increased (Li et al, 2016).…”
mentioning
confidence: 93%
“…Currently, techniques such as acoustic emission experiments, acoustic logging, and seismic monitoring, which are based on elastic wave theory, have become important methods for detecting underground structures, oil and gas minerals, and geothermal resources. However, the changes in pore structure can significantly impact the elastic frame moduli of naturally occurring rocks, resulting in changes in their elastic wave velocities [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The pore aspect ratio (AR; the ratio of the minor axis to the major axis) dependence of velocities of crustal rocks, affecting the energy exchange between the formation and pore fluids, has been widely reported [5,[10][11][12][13]. The power relationship between elastic wave velocities and pore AR has been proposed in the theoretical model (e.g., [14,15]) and rock physics experiments at the core scale (e.g., [4,8]). However, the frequency dependence of velocities can lead to errors and difficulties in the dynamic elastic parameters of rocks when attempting to apply the laboratory results in the ultrasonic frequency band (0.1 MHz-10 MHz) to the acoustic well-logging interpretation in the mediumfrequency range (20 Hz-200 kHz) [16][17][18][19] and seismic exploration (~100 Hz) [20].…”
Section: Introductionmentioning
confidence: 99%